Vegetation Dynamics and Diversity Status in Mughal Garden Wah, Pakistan: Vegetation Dynamics and Diversity (Biological Sciences - PJSIR, 2019)
Classification and ordination of vegetation of Mughal Garden, Wah, Pakistan was done along with assessment of diversity status. A total of 45 species were recorded in vegetation survey belonging to 24 families with Asteraceae and Poaceae being the largest families. Herbs dominated the flora of Wah Garden by 44.4%, shrubs 15.5%, trees 13.3%, grasses 11.1%, creeping herbs 11.1%, ferns 2.2% and aquatic herbs 2.2%. About 35.5% species were annuals, 28.8% perennials, 13.3% annuals or perennials, 8.8% annuals or biennials, 8.8% deciduous, 2.2% coniferous and evergreen species. In case of life form of species, Therophytes and Megaphanerophytes were the most prevalent among species indirect ordination techniques TWINSPAN and DCA were employed that produced two major groups which were further divided into five communities and three major groups, respectively. Shannon-Wiener diversity index, Simpson Index of diversity and Hill?s N1 and N2 diversity numbers were calculated and verified by data attribute plot through DCA suggesting reduced species diversity as Shannon-Wiener diversity index ranged between 0 and 1.67 due to increased anthropogenic activity. The outcome of this research will be useful in providing information on identification of species that are present, their distribution patterns, and classification which would help in management and conservation of native vegetation in future.